High Prevalence of Lesions of Systemic Hypertension in Bile-Extracted Asiatic Black Bears (Ursus thibetanus) and Associated Renal Disease - Monica K. H. Bando; O. Lynne Nelson; Kyle Taylor; Rance Sellon; Clark Kogan; Jill Robinson; Emily Drayton; Claudia Hartley; David Donaldson; Chris Linney; Hannah Stephenson (Animals)
Approximately 17,000 bears undergo bile extraction in facilities across Asia for traditional medicines despite the availability of proven alternatives. Bears are confined to cages and bile harvested from the gallbladder via needle aspiration, implanted catheters, or transabdominal fistulas. Bile-extracted bears develop numerous detrimental conditions, including abnormal repetitive behaviors, emaciation, dental disease, cholecystitis, hernias, abscesses, and neoplasia. A high prevalence of aortic dilation, commonly seen with systemic hypertension, was reported in bile-extracted bears, and aortic aneurysm rupture/dissection was the third leading cause of death in a population of 600 formerly bile-extracted bears. A high incidence of renal disease, a common cause of systemic hypertension in other species, was also identified in this population. We hypothesized that renal disease was positively correlated with lesions of systemic hypertension in bile-extracted bears. Archived medical records, imaging, and samples from 180 formerly bile-extracted bears were analyzed. Hypertensive retinopathy, left ventricular hypertrophy, and aortic dilation were used as validated correlates of systemic hypertension. The majority (76.1%) of bears exhibited at least one systemic hypertension lesion, and 62.8% had two or more lesions. Left ventricular hypertrophy was most common, followed by aortic dilation/aneurysm. Lesions of systemic hypertension were positively correlated to renal disease parameters of serum creatinine and renal histopathology. Understanding the etiology of systemic hypertension in this population is critical due to consequent comorbidities and increasing numbers of bile-extracted bears finding their way to sanctuary.